PEMANFAATAN KULIT BUAH CARICA UNTUK PEKTIN DI UD. YUASSA FOOD BERKAH MAKMUR - , NURUL CHASANAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Carica syrup production process in UD Yuasa Food Berkah Makmur generates byproducts such as carica fruit leather. Carica fruit skin but cause no harm to the environment due to the foul smell of moisture contained many which reached 93.12%, therefore it is necessary to minimize the skin of the fruit Carica. Skin carica fruit contains carbohydrates and crude fiber, respectively for 4.46% and 1.42% which can be used as a source of pectin. This thesis aims to determine the production process of carica syrup, knowing what processes are generating carica fruit leather, determine levels of pectin extracted from Carica fruit skin and determine the added value of the use carica fruit peel for pectin. The process of making pectin conducted several stages of preparation of raw materials, extraction of pectin, coagulation, deposition of pectin, pectin washing, drying and grinding. Implementation research using solvent extraction method with acetic acid. Carica smoothed skin and corresponding variables specified extraction and material filtered with filter paper in hot conditions. The filtrate from the filtration coupled with NaOH to form a precipitate. Purification was carried out by using Ca chloride then dried in an oven at 100 Â° C until a constant weight is obtained. Weighed dry pectin as a result. The results showed that the pectin is produced from the skin of the fruit Carica is 13.14%. UD Yuasa Food Blessing Prosper carica produce 200 kg per day so that the skin can produce as much pectin 26.28 kg per day. Utilization of Carica fruit skin as pectin will greatly help the industry because it can reduce the amount of skin that is not utilized carica fruit and reduce distribution costs carica fruit leather disposal to landfill and provide added value to the industry. Price pectin reached 200,000,-per kg, if the company is sold to benefit Rp 5.256 million, - per day.